2011
DOI: 10.1186/cc9413
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the Toll-interacting protein gene are associated with susceptibility to sepsis in the Chinese Han population

Abstract: IntroductionDeregulated or excessive host immune responses contribute to the pathogenesis of sepsis. Toll-like receptor (TLR) signaling pathways and their negative regulators play a pivotal role in the modulation of host immune responses and the development of sepsis. The objective of this study was to investigate the association of variants in the TLR signaling pathway genes and their negative regulator genes with susceptibility to sepsis in the Chinese Han population.MethodsPatients with severe sepsis (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 33 publications
4
37
1
Order By: Relevance
“…For example, humans with a rare Tollip haplotype have reduced Tollip levels and elevated risks for infection and tuberculosis (41). Other studies suggest that Tollip variants may be associated with elevated risks of sepsis, dermatitis, and pulmonary fibrosis (43)(44)(45). Our wound-healing model clearly demonstrates a key role for Tollip in the resolution of inflammation during tissue repair.…”
Section: Discussionmentioning
confidence: 64%
“…For example, humans with a rare Tollip haplotype have reduced Tollip levels and elevated risks for infection and tuberculosis (41). Other studies suggest that Tollip variants may be associated with elevated risks of sepsis, dermatitis, and pulmonary fibrosis (43)(44)(45). Our wound-healing model clearly demonstrates a key role for Tollip in the resolution of inflammation during tissue repair.…”
Section: Discussionmentioning
confidence: 64%
“…MyD 88 SNP allele and genotypes were found statistically insignificant between two groups. As a result, Song et al (10) showed that MyD 88 SNP was not a risk factor for sepsis in China population. Von Bernuth et al (8) discovered 3 different mutations in MyD 88 deficient children who are susceptible to pyogenic bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on MyD 88 SNP and sepsis relationship in human is limited. Song et al (10) showed that gene variations of TLR signaling pathways and negative regulators of these pathways increase susceptibility to sepsis. That study was conducted between February 2006 and November 2009, in China.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed similar result that there were no significant differences of TLR4 Asp299Gly between DHF/DSS and control group, or severity of meningococcal infection and outcome of gram negative sepsis [20][21][22][23] . Metaanalysis studies in Caucasian and in China found that there were not strong correlation between sepsis and TLR4 Asp299Gly polymorphism [24][25][26][27] . Race, ethnic and geography seem to affect the frequency of TLR4 Asp299Gly polymorphism.…”
Section: Discussionmentioning
confidence: 99%